Investigation of in-vitro antidiabetic and antioxidant properties of Lagerstroemia thorelli leaf extract - Taki, Ehtesham Sabet (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.